The contribution of mouse models to understanding the pathogenesis of spinal muscular atrophy. - Sleigh, J; Gillingwater, T; Talbot, K (2011)
Spinal muscular atrophy (SMA), which is caused by inactivating mutations in the survival motor neuron 1 (SMN1) gene, is characterized by loss of lower motor neurons in the spinal cord. The gene encoding SMN is very highly conserved in evolution, allowing the disease to be modeled in a range of species. The similarities in anatomy and physiology to the human neuromuscular system, coupled with the ease of genetic manipulation, make the mouse the most suitable model for exploring the basic pathogenesis of motor neuron loss and for testing potential treatments. Therapies that increase SMN levels, either through direct viral delivery or by enhancing full-length SMN protein expression from the SMN1 paralog, SMN2, are approaching the translational stage of development. It is therefore timely to consider the role of mouse models in addressing aspects of disease pathogenesis that are most relevant to SMA therapy. Here, we review evidence suggesting that the apparent selective vulnerability of motor neurons to SMN deficiency is relative rather than absolute, signifying that therapies will need to be delivered systemically. We also consider evidence from mouse models suggesting that SMN has its predominant action on the neuromuscular system in early postnatal life, during a discrete phase of development. Data from these experiments suggest that the timing of therapy to increase SMN levels might be crucial. The extent to which SMN is required for the maintenance of motor neurons in later life and whether augmenting its levels could treat degenerative motor neuron diseases, such as amyotrophic lateral sclerosis (ALS), requires further exploration.